(untitled) (GYMNASIUM, 2017)
Achieving this paper provides general information about a sample of athletes who practice handball in the national handball team regarding performance and degree of dispersion and correlation of test values. To highlight the athletes’ biological parameters were used as research methods: bibliographic study, observation, results recording, statistical and mathematical method. Collection and recording of data were performed at the National Center for Sports Medicine.